Mental Health Psychoeducation: Effort to Increase Mental Health Literacy in Adolescence - Alqifari, Salman; Amellia, Riska Azza; Septiany, Fildzah Ayudhia; Merida, Sarita Candra (Universitas Negeri Semarang, 2024)
Some adolescents demonstrate a deficiency in awareness regarding mental health. This deficit in knowledge is attributable to a lack of mental health literacy. The objective of this research is to ascertain the efficacy of psychoeducation in enhancing mental health literacy among teenagers belonging to the Karang Taruna organisation. Eighteen participants were selected using a purposive sampling technique, with the criteria being young men or women who were members of Karang Taruna. The methodology employed in this study is a quasi-experimental design with a one-group pretest-posttest. The results of the data analysis, conducted using the Paired Sample T-test, indicating a statistically significant difference between the pretest and posttest results. The results demonstrated a notable increase in scores from the pretest to the posttest following the administration of psychoeducation. This outcome substantiates the efficacy of psychoeducation in enhancing public awareness about mental health literacy. It is anticipated that by fostering mental health literacy, individuals will be better equipped to identify, comprehend, and avert issues pertaining to mental health.